2019
DOI: 10.1021/acs.jced.9b00576
|View full text |Cite
|
Sign up to set email alerts
|

Solvatochromic Absorbance and Fluorescence Probe Behavior within Ionic Liquid + γ-Butyrolactone Mixture

Abstract: The co-solvent modified ionic liquid (IL) systems offer favorable physicochemical properties, which render them as suitable solvents for several technological applications. Therefore, it is an utmost need to achieve a full understanding of such systems before their further applications. Here, solvation properties of 1-butyl-3-methylimidazolium tetrafluoroborate, [bmim]­[BF4], and γ-butyrolactone (GBL) mixture, which is an important binary mixture for several electrochemical applications, are explored by multip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 80 publications
0
11
0
Order By: Relevance
“…84 It has variety of applications such as in the enhancement of the capacity and conductivity of lithium ion batteries, and in the synthesis of solvents such as N-methyl-2pyrrolidone (NMP). 85 Hong et al reported the first successful polymerizations of γbutyrolactone under ambient pressure using a lanthanum catalyst (entry 7), which yielded cyclic and linear polymers depending on the [monomer]:[catalyst]:[co-initiator] ratios. Subzero temperatures (around −40 °C) reduced the entropic penalty of the reaction and different lanthanide metals were tested.…”
Section: ■ Scope Of Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…84 It has variety of applications such as in the enhancement of the capacity and conductivity of lithium ion batteries, and in the synthesis of solvents such as N-methyl-2pyrrolidone (NMP). 85 Hong et al reported the first successful polymerizations of γbutyrolactone under ambient pressure using a lanthanum catalyst (entry 7), which yielded cyclic and linear polymers depending on the [monomer]:[catalyst]:[co-initiator] ratios. Subzero temperatures (around −40 °C) reduced the entropic penalty of the reaction and different lanthanide metals were tested.…”
Section: ■ Scope Of Reviewmentioning
confidence: 99%
“…γ-Butyrolactone is a known petrochemical product and promising biomaterial which can be produced from succinic acid . It has variety of applications such as in the enhancement of the capacity and conductivity of lithium ion batteries, and in the synthesis of solvents such as N -methyl-2-pyrrolidone (NMP) …”
Section: General Synthetic Approaches: Ring Closure and Ring Expansionmentioning
confidence: 99%
“…6 , 7 and 8 . The computed IR spectrum in animated modes was found to be compatible with few significant experimental vibrational signals in the FTIR spectra of the compounds [ 51 ]. The slight difference between theoretical and experimental frequencies is due to theoretical values being acquired in gas phase and experimental values being obtained in solid phase and also due to neglecting the incompleteness and anharmonicity of the basis set.…”
Section: Resultsmentioning
confidence: 84%
“…The 1 H-NMR spectra for all the compounds were also obtained through GIAO calculation, as shown in Figs. 10 , 11 and 12 [ 51 ]. Frontier molecular orbitals (FMOs) are significant factors for explaining chemical behavior; hence, they were also computed theoretically.…”
Section: Resultsmentioning
confidence: 99%
“…The HOMO (−4.2308 eV) to LUMO (−1.6620 eV) energy gap (∆E) was calculated to be 2.5687 eV. The spatial arrangements of the HOMO-LUMO, associated energies, and gap are represented in Figure 19 [52][53][54]. Some molecular parameters in the gas phase, based on HOMO-LUMO and optimized geometry, are presented in Table 8.…”
Section: Mds Analysismentioning
confidence: 99%